IDENTIFIKASI MORFOLOGI DAN ANATOMI TANAMAN MANGGIS (Garsiania mangostana L.) DI KECAMATAN KULAWI KABUPATEN SIGI - Yustiono, Doni; Adelina, Enny; Syamsiar, Syamsiar (AGROTEKBIS, 2018)
This study aimed to investigate the characteristics of mangosteen based on its leaf morphology and anatomy in Kulawi sub district. The morphology observations were made in the Bolapapu, Boladangko and Namo villages while the anatomy were analyzed in the Plant Pest and Disease Science laboratory, Faculty of Agriculture Tadulako University from Mei-Augustus 2017. the morphological and anatomical character observed were based on the cluster analyses and presented in the form of dendogram. The results of the cluster showed that in the three villages at the distance of 0.58, there are five accessions i.e. Bolapapu-02, Bolapapu-07, Bolapapu-10, Boladangko-01 and Namo-07.